Pengaruh Layanan e-Samsat terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di UPTD Pependa Medan Selatan - Wijaya Turnip, Mikael; Humaizi; Muhammad Husni Thamrin (Universitas Medan Area, 2024)
The electronic Samsat application (e-Samsat) at the Regional Revenue Management Technical Implementation Unit (UPTD) Medan Selatan is expected to enhance motor vehicle taxpayers' compliance. This compliance is crucial for optimizing regional tax revenue and supporting regional development. However, low taxpayer awareness and the complexity of payment procedures remain challenges that need to be addressed. This study aims to analyze the impact of the e-Samsat service on taxpayer compliance. The research employs a quantitative approach using a survey method, collecting data through questionnaires distributed to motor vehicle taxpayers in the UPTD Medan Selatan area. The analysis technique used is simple linear regression to determine the influence of the e-Samsat service on taxpayer compliance. The results show that the e-Samsat service positively affects compliance. The application facilitates payment access, reduces waiting times, and increases taxpayer understanding of their tax obligations. However, technical issues and a lack of understanding of how to use the application still pose challenges. Therefore, the government is advised to intensify outreach efforts, improve technological infrastructure, and enhance service quality to maximize the positive impact of e-Samsat.